A perspective of Mycobacterium Tuberculosis resistance on patients with retreat in Madagascar - Anjara Mihaja NANDIMBINIAINA, Jocelyn Rakotomizao, Rakotoson Joelson Lovaniaina, ANDRIANASOLO Radonirina Lazasoa, RAHARIMANANA Rondro Nirina, Harison Michel TIARAY*, Kiady RAVAHATRA, Jobeline RAJAOARIFETRA, Oninala Fenitra RAKOTONDRASOA, Iantsotiana Davidson RAKOTONDRABE, Marie odette RASOAFARANIRINA (Innovative Journal of Medical and Health Sciences, 2020)
Introduction: Despite advances in diagnostic and therapeutic way, drug-resistant tuberculosis is an increasingly worrying threat. Several studies suggest that one of the risk factors for carrying resistant Mycobacterium tuberculosis is the history of anti-tuberculosis treatment. The objective of our study is to describe the Resistance Profile of Mycobacterium Tuberculosis of patients in retreatment in Madagascar. Methods: This is a descriptive and retrospective study, carried out from January 2014 to September 2018 (45 months). All the cases of re-treatement recorded in the database of the National Tuberculosis Control Program in Madagascar were included in the study. Results: We gathered 1456 cases, the average age was 40 years, there was a male predominance(sex ratio of 2.32). In the 1302 cases where the category was specified, there was a predominance of relapse (76.57%). According to the culture, the incidence of rifampicin resistance was 05.36% (78/1456) including 83.33% of cases of multi-resistant tuberculosis (MDR-TB) (65/78). The incidence of isoniazid monoresistance was 05.49% (80/1456). Carrying MDR-TB is much more important for patients who have failed (69.43%). The GeneXpert mtb/RIF enabled us to detect more cases of Rifampicine monoresistance (97 cases). Conclusion: cases of retreatment is a real source of the emergence of MDR-TB in Madagascar, especially cases of failure and relapse. Which is consistent with the data in the literature. The treatment effectiveness of new cases must be maximum to prevent these cases of retreatment. Key words: drug resistance–Madagascar–profil–tuberculosis